Outdoor pollen is a trigger of child and adolescent asthma emergency department presentations: A systematic review and meta‐analysis. Issue 8 (2nd March 2018) - Erbas, B.; Jazayeri, M.; Lambert, K. A.; Katelaris, C. H.; Prendergast, L. A.; Tham, R.; Parrodi, M. J.; Davies, J.; Newbigin, E.; Abramson, M. J.; Dharmage, S. C.
Abstract: Background: In the context of increased asthma exacerbations associated with climatic changes such as thunderstorm asthma, interest in establishing the link between pollen exposure and asthma hospital admissions has intensified. Here, we systematically reviewed and performed a meta‐analysis of studies on pollen and emergency department (ED) attendance. Methods: A search for studies with appropriate search strategy in MEDLINE, EMBASE, Web of Science and CINAHL was conducted. Each study was assessed for quality and risk of bias. The available evidence was summarized both qualitatively and meta‐analysed using random‐effects models when moderate heterogeneity was observed. Results: Fourteen studies were included. The pollen taxa investigated differed between studies, allowing meta‐analysis only of the effect of grass pollen. A statistically significant increase in the percentage change in the mean number of asthma ED presentations (MPC) (pooled results from 3 studies) was observed for an increase in 10 grass pollen grains per cubic metre of exposure 1.88% (95% CI = 0.94%, 2.82%). Time series studies showed positive correlations between pollen concentrations and ED presentations. Age‐stratified studies found strongest associations in children aged 5‐17 years old. Conclusion: Exposure to ambient grass pollen is an important trigger for childhood asthma exacerbations requiring ED attendance. As pollen exposure is increasingly a problem especially in relation to thunderstorm asthma, studies with uniform measures of pollen and similar analytical methods are necessary to fully understand its impact on human health.